Receptor modelling and risk assessment of volatile organic compounds measured at a regional background site in South Africa. (January 2018) - Jaars, Kerneels; Vestenius, Mika; van Zyl, Pieter G.; Beukes, Johan P.; Hellén, Heidi; Vakkari, Ville; Venter, Marcell; Josipovic, Miroslav; Hakola, Hannele
Abstract: Volatile organic compounds (VOCs) can have significant impacts on climate and human health. Certain VOCs are proven to be carcinogenic and toxic, which can affect human health directly and indirectly. In order to develop climate change reduction strategies and to assess the impacts of VOCs on human health, it is crucial to determine the sources of VOCs, which can be emitted from biogenic and anthropogenic sources. The aim of this study was to perform source apportionment using positive matrix factorisation (PMF) analysis on VOC data collected at a regional background location affected by the major sources in the interior of South Africa, which include the western- and eastern Bushveld Igneous Complex, the Johannesburg-Pretoria metropolitan conurbation, the Vaal Triangle, the Mpumalanga Highveld and also a region of anti-cyclonic recirculation of air mass over the interior of South Africa. In addition, a risk assessment study was also performed in view of the major source regions affecting Welgegund in order to quantify the impacts of anthropogenic VOCs measured at Welgegund on human health. Measurements were conducted at the Welgegund measurement station located on a commercial farm approximately 100 km west of Johannesburg for a period of more than two years. PMF analysis revealed ten meaningful factor solutions, of which five factors were associated with biogenic emissions and five with anthropogenic sources. Three of the biogenic factors were characterised by a specific biogenic species, i.e. isoprene, limonene and 2-methyl-3-buten-2-ol (MBO), while the other two biogenic factors comprised mixtures of biogenic species with different tracer species. The temporal factor contribution for the isoprene, limonene and MBO factors correlated relatively well with the seasonal wet pattern. One anthropogenic factor was associated with emissions from a densely populated anthropogenic source region to the east of Welgegund with a large number of industrial activities, while another anthropogenic factor could be related to coal combustion. An anthropogenic factor was also identified that reflected the influence of solvents on atmospheric VOC concentrations, while two anthropogenic factors were determined that indicated the influence of farming activities in close proximity to Welgegund. A lifetime cancer risk- (LCR) and non-cancer hazard ratio (HR) assessment study conducted for VOCs measured at Welgegund in relation to three source regions indicated that the non-cancerous influence of VOCs measured in the source regions is significantly lower compared to the cancerous influence of these species on human health, which raises concern. However, LCR values were within an acceptable range. Factor analysis performed in this paper also identified sources that could be targeted to minimise VOC-related LCRs and HRs e.g. benzene-related cancers can be reduced by targeting incomplete combustion sources and coal combustion. Highlights: PMF analysis revealed five biogenic and five anthropogenic factors. Three biogenic factors represented isoprene, limonene and MBO. Anthropogenic factors included a megacity, coal combustion, solvents and farming. Lifetime cancer risks were within an acceptable range. Benzene-related cancers can be reduced by targeting combustion sources.